2019
DOI: 10.1021/acs.macromol.8b02289
|View full text |Cite
|
Sign up to set email alerts
|

Sulfo-Phenylated Polyphenylenes Containing Sterically Hindered Pyridines

Abstract: We systematically investigated the effect of incorporating a sterically hindered pyridyl group into a sulfophenylated polyphenylene to control the polymer's physicochemical properties through acid−base interactions. Homopolymers with similar molecular weights and comparable structures that vary by only one atom (N− vs C−) per repeat unit along the polymer chain were prepared. Compared to a non-pyridyl reference membrane, incorporation of a pyridyl group improves the oxidative stability against free radicals, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…Previously reported chemical stability data showed that sulfonated phenylated polyphenylenes can withstand 1000 h OCV stress test at exceptionally low degradation rates of 0.16 mV h À1 , 23 without incorporation of radical scavengers. This excellent stability in combination with the promising performance shown in the present study thereby represents a signicant step in the development of next-generation MEAs for hydrogen fuel cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously reported chemical stability data showed that sulfonated phenylated polyphenylenes can withstand 1000 h OCV stress test at exceptionally low degradation rates of 0.16 mV h À1 , 23 without incorporation of radical scavengers. This excellent stability in combination with the promising performance shown in the present study thereby represents a signicant step in the development of next-generation MEAs for hydrogen fuel cells.…”
Section: Discussionmentioning
confidence: 99%
“…A common polymer architecture employed in such materials is the polyphenylene backbone, which unlike preceding poly(arylene ether)s and numerous derivatives thereof, contain no backbone linkages particularly susceptible to chemical degradation. 1 For example, Skalski et al, 19 Adamski et al, 20 Miyake et al, 21 Shiino et al, 22 Xu et al, 23 and Shimizu et al, 24 reported PEMs with best-in-class chemical durability, all based on a polyphenylene backbones. Compared to PFSAs, however, the reported ex situ and in situ durabilities of hydrocarbon polyphenylene-based PEMs have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon adding a 4-fold excess of tetraphenylcyclopentadienone 4 to the imide diyne 3, a full conversion of the terminal alkyne to give compound 5 was observed by 13 C-NMR spectroscopy (see ESI86). The conditions required for this reaction were found to be 260 °C in diphenyl ether for 72 h. Buoyed by this observation, we then prepared a bifunctional diene 6 in Scheme 2 according to literature procedures 18,35 . Compound 6 underwent a Diels-Alder polymerization with diyne 3 to yield the polymer PI-1, a highly aromatic soluble polyimide.…”
Section: Diels-alder Polymerizationmentioning
confidence: 98%
“…Open 31,66,67,69,72,73,212,213 This article is licensed under a Creative Commons Attribution 3.0 Unported Licence.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%